Advancing Hepatocellular Carcinoma Management Through Peritumoral Radiomics: Enhancing Diagnosis, Treatment, and Prognosis - Huang Y; Qian H (Journal of Hepatocellular Carcinoma)
Yanhua Huang,1 Hongwei Qian2,3 1Department of Ultrasound, Shaoxing People’s Hospital, Shaoxing, People’s Republic of China; 2Department of Hepatobiliary and Pancreatic Surgery, Shaoxing People’s Hospital, Shaoxing, People’s Republic of China; 3Shaoxing Key Laboratory of Minimally Invasive Abdominal Surgery and Precise Treatment of Tumor, Shaoxing, People’s Republic of ChinaCorrespondence: Hongwei Qian, Department of Hepatobiliary and Pancreatic Surgery, Shaoxing People’s Hospital, 568 Zhongxing North Road, Shaoxing, 312000, People’s Republic of China, Email qhwsxsrmyy@163.comAbstract: Hepatocellular carcinoma (HCC) is the most common primary liver cancer and is associated with high mortality rates due to late detection and aggressive progression. Peritumoral radiomics, an emerging technique that quantitatively analyzes the tissue surrounding the tumor, has shown significant potential in enhancing the management of HCC. This paper examines the role of peritumoral radiomics in improving diagnostic accuracy, guiding personalized treatment strategies, and refining prognostic assessments. By offering unique insights into the tumor microenvironment, peritumoral radiomics enables more precise patient stratification and informs clinical decision-making. However, the integration of peritumoral radiomics into routine clinical practice faces several challenges. Addressing these challenges through continued research and innovation is crucial for the successful implementation of peritumoral radiomics in HCC management, ultimately leading to improved patient outcomes.Keywords: hepatocellular carcinoma, peritumoral radiomics, diagnostic Imaging, artificial intelligence, precision medicine